Identifikasi Bahan dan Pembuatan Noken Tas Tradisional Serat Kayu Pada Masyarakat Lokal Kampung Rhepang Muaif, Distrik Nimbokrang Kabupaten Jayapura - Keiluhu, Henderina J.; Chrystomo, Linus Y.; Yuliana, Sarah; Silitonga , Ronauli (Jurnal Biologi Papua, 2024)
Local people in Rhepang Muaif Village, Nimbokrang District, Jayapura Regency usually use forest tree bark of three species, especially Dakwab wood, as raw material for noken, Papuan traditional woven bags. This study aimed to 1) scientifically identify the species of trees used for noken, 2) describe how to process fiber as a raw material, and 3) reveal the source of natural dyes used. Data collection was carried out using survey method, semi-structured interviews and participant observation. The result shows that in Rhepang Muaif, some species are used as raw material for noken, mainly species of Dakwab tree (Grewia paniculata). Dakwab fibers are generally coloured with natural dyes derived from Merei plant (Bixa orellana) for red colour and turmeric (Curcuma domestica) for yellow colour. The process of utilizing Dakwab bark as a noken fiber material starts from debarking the tree, stripping the bark, then washing, drying, and making the fiber from tree bark, later colouring if necessary and finally woving or knitting the fiber to become the bag.